Role and challenges to digital technologies in community health promotion programs in Italy during the COVID-19 pandemic: a multiple embedded case study protocol - Del Riccio, Marco; Costantini, Luigi; Guasconi, Massimo; Casella, Giovanna; Fanfani, Alice; Cosma, Claudia; Mindrican, Paula; Bonaccorsi, Guglielmo; Corradini, Elena; Artioli, Giovanna; Sarli, Leopoldo; Laverack, Glenn; et al. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Due to the COVID-19 pandemics, The Italian League Against Cancer (LILT), a national federation of local associations promoting cancer prevention, had to face the challenge to find new ways and technologies to promote health in their territories. This study aims to explore how LILT associations led their health promotion interventions during the COVID-19 pandemic and to understand which interventions had a greater impact, for which population group, and why. Methods: In this descriptive multiple embedded case study, each case will focus on the activities of a local LILT association and their collaborators on the perception and experience of the use of digital technology for health promotion and prevention, through interviews, observations, and a study of products and artifacts. A general overview of each case study will be provided, along with an introduction of the unit(s) of more in-depth analysis. The logical models that emerge from the analysis of each case will be described by using realist analysis, producing a list of possible CMO configurations (Context; Mechanisms; Outcomes). The final report will consist of a cross-case analysis (a comparison between the different case studies). Discussion: This multiple case study will help generate a first "theory of the use of digital technology in health promotion in local LILT communities. The observation of what local LILT associations in Italy have done during COVID-19 will help identify new and useful health promotion strategies based on these technologies.